IMPROVING FUNCTIONAL TEXT WRITING ACHIEVEMENT BY USING FOUR SQUARE STRATEGY AT SMK NEGERI 2 SEKAYU - Irlina (Language and Education Journal, 2021)
The fact that English writing skill in Indonesia is still low encouraged the writer to conduct this study concerning vocational high school students. Four Square strategies in prewriting activities help students to write, especially in writing functional text. The objective of this study was to see if there was a substantial difference in writing achievement between students who were taught with the Four Square strategy and those who were not. The quasi experimental approach was applied in this research. The population of SMK Negeri 2 Sekayu’s eleventh graders in the academic year 2021/2022 with a total of 217 students. From this group, 60 students were chosen as the sample and divided evenly into two groups, the experimental and control groups. The Four Square strategy was used to teach the experimental group, whereas the control group received no treatment. However, all the students in the two groups were given writing tests before and after the application of the two strategies. A t-test was used to assess the data collected. The result showed that the experimental group outperformed the control group with a significant mean difference of 23.82 (p < 0.00). These results indicated that the Four Square strategy was effective in improving the students’ writing achievement